Tropos logikos: Gustav Spet’s Philosophy of Historiography - Steiner, Peter (Dějiny – teorie – kritika, 2008)
Gustav G. Spet (1879–1937) is one of those formidable Russian thinkers who, in the early years of the last century, orchestrated a revolutionary paradigm shift across a broad swath of the humanities and social sciences, which is still reverberating today. We lack, however, a comprehensive view of the manifold heterogeneity of his intellectual endeavours. This article focuses on one prominent lacuna in our knowledge of Spet: the theory of history that he advanced in the 1910s. In many respects his theory anticipated the ‘linguistic turn’ that occurred in Western historiography during the last quarter of the twentieth century, which is most often identified with Hayden White. But whereas White analyzes the historian’s discourse in terms of tropology and narratology, for Spet predication is the key logical mechanism generating the production of texts about the past. The divergence of these two approaches, the article concludes, can be explained through the hidden Kantian underpinnings of White’s thought, which contrasts sharply with the explicit Hegelianism of Spet’s theorizing.